On iteration stability of the Birkhoff center with respect to power 2 - Polulyakh, E. O.; Vlasenko, I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
It is proved that the Birkhoff center of a homeomorphism on an arbitrary metric space coincides with the Birkhoff center of its power 2.